The impact of smoking on individual health expenditures: a case study of Namibia - Chisha, Zunda (Health Economics Unit, 2017)
Background: The increased smoking prevalence in some parts of the world, particularly in Low and Middle Income Countries (LMICs) is a major concern among tobacco control advocates and governments. The higher smoking-related disease prevalence associated with this is expected to fall among the sub-populations least able to pay for healthcare services in LMICs. This, in turn, will perpetuate the vicious cycle of poverty and disease. The current study contributes to developing an understanding of the socioeconomic disparities in smoking in Namibia and their potential association with per capita health-related expenditures. Method: Data from the Namibia 2013 Demographic and Health Survey, a nationally representative survey, are used in the study. Three main variables for healthcare costs are constructed, namely out-patient disease (OPD) costs, inpatient disease (IPD) costs and total out of pocket (OOP) payments. Concentration curves and indices are estimated for all three variables as well as for smoking intensity and smoking prevalence. Further, three Tobit regression models are run to examine the associations of the different healthcare costs with smoking intensity. Results: The concentration index of smoking prevalence is estimated at -0.05 compared to -0.18 for smoking intensity. Thus, both smoking prevalence and smoking intensity, in relation to their socioeconomic status, are concentrated among the poor. In contrast, the concentration index of OPD healthcare costs is calculated at 0.34 compared to 0.65 for IPD healthcare costs reflecting disproportionately higher healthcare costs among the rich. The concentration index of the overall total annual OOP payments is 0.55. Tobit regression analysis, however, does not find any statistically significant relationship between the smoking intensity and the amount spent on health care costs, regardless of whether these were IPD, OPD healthcare costs or total OOP payments. Conclusion: Namibia's current policies on demand reducing tobacco control policies can be strengthened by these findings. Smoking is an important determinant of several non-communicable diseases and has the potential to exacerbate health care costs across socioeconomic strata. Understanding the socioeconomic disparities in smoking is imperative for developing appropriate interventions against smoking.